Cultural disruption and challenges for anthropology in the development of multicultural communities (ETNOSIA : Jurnal Etnografi Indonesia, 2020)
This article intends to discuss the phenomenon of cultural disruptions due to globalization and the industrial revolution 4.0 which have paradoxical consequences for empirical life and in the academic world, especially in the field of anthropology. This study uses a library method with interpretive analysis techniques. The results concluded that globalization and the industrial revolution 4.0 had fundamentally changed the order of the people's cultural values. This is a challenge for anthropology to reflect on epistemology and axiology as a logical consequence of changes in the ontology. In the context of Indonesia, the presence of anthropology is expected to be able to explore the plurality of national culture that can be narrated on the academic stage. At the same time, it can be also a productive cultural capital to overcome the challenges of diversity, becoming a driver of change, and strengthening national identity.
Keywords: Cultural Disruptions; Globalization; Culture Capital; multiculturalism; Anthropology.